Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs): a new heterogeneous and recyclable catalyst for the one pot synthesis of 1,4-disubstituted-1,2,3-triazoles in water - Chavan, Pramod V.; Pandit, Kapil S.; Desai, Uday V.; Kulkarni, Makarand A.; Wadgaonkar, Prakash P. (RSC Advances, 2014)
Cellulose supported cuprous iodide nanoparticles (Cell-CuI NPs) have been demonstrated for the first time as an efficient heterogeneous catalyst in the click synthesis of 1,4-disubstituted 1,2,3-triazoles by a one-pot three component reaction between aralkyl/alkyl bromides, alkynes and sodium azide in water. The catalyst has been characterized by XRD, HRTEM, SEM, ICP-AES, EDS as well as IR spectroscopy. It was found to be reusable for five consecutive runs without significant loss of activity.